Two new species of Coprinopsis from Kerala State, India - Ganga, K. G. Greeshma; Manimohan, Patinjareveettil; Latha, K. P. Deepna (Phytotaxa, 2022)
Two new species, Coprinopsis minuta and C. squamulosa, are described from Kerala State, India, on the basis of both morphology and molecular data. Comprehensive descriptions, photographs of both the basidiocarps and the microscopic structures, and discussions are provided. Sequences of both the nuclear ribosomal internal transcribed spacer region (nrITS) and the nuclear ribosomal large subunit (nrLSU) region of the two new species were obtained and used in the BLASTn searches. Phylogenetic analysis of the nrITS sequences revealed the novelty of the species as well as their placement in the section Coprinopsis.